Molecular and cellular changes in skin and muscle during metamorphosis of Atlantic halibut (Hippoglossus hippoglossus) are accompanied by changes in deiodinases expression - Campinho, Marco António (2014)
Flatfish metamorphosis is the most dramatic postnatal developmental event in teleosts. Thyroid hormones (TH), thyroxine (T4) and 3,3′-5′-triiodothyronine (T3) are the necessary and sufficient factors that induce and regulate flatfish metamorphosis. Most of the cellular and molecular action of TH is directed through the binding of T3 to thyroid nuclear receptors bound to promoters with consequent changes in the expression of target genes. The conversion of T4 to T3 and nuclear availability of T3 depends on the expression and activity of a family of 3 selenocysteine deiodinases that activate T4 into T3 or degrade T4 and T3.